Early experience with intravenous immunoglobulin treatment in Wegener's granulomatosis with ocular involvement - Blum, Marcus; Andrassy, Konrad; Adler, Detlev; Hartmann, Marius; Völcker, Hans Eberhard (Graefe's archive for clinical and experimental ophthalmology, 1997)
• Background: Pooled intravenous gammaglobulin (IVIg) was reported to be effective in the treatment of Wegener's granulomatosis (WG). No reports have been made on the effects of this new treatment on ocular manifestations of WG. • Method: IVIg treatment was given to two patients suffering from WG with ocular involvement after several other treatment regimes had failed. • Results: Although the systemic disease was under control, the ocular symptoms of both patients worsened during and after IVIg treatment. In one case an adverse effect consisting of retinal vasculitis was noted on two occasions. • Conclusion: Although beneficial effects of IVIg treatment on WG have been previously described, the two cases with ocular involvement presented here did not reveal any positive response. Paradoxical and unpredictable reactions cannot be ruled out. Thus, patients treated with IVIg should be closely surveyed by an ophthalmologist.